GRAFANA-BASED DOMAIN EXPIRATION AND SSL CERTIFICATE MONITORING SYSTEM FOR PREVENTIVE SECURITY - Asyiyah, Nur; Putra Pratama, Hafiyyan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
Abstract: Manual management of domain validity periods and SSL certificates is prone to human error and can cause service disruptions, as was the case at PT XYZ. A reactive approach that relies on vendor notifications has proven to be insufficient to ensure operational continuity. This research aims to design and implement an automated monitoring system to transform this manual approach into a preventive and proactive security framework. The method used is the implementation of an open-source stack consisting of Prometheus to collect metrics from specialized exporters (Blackbox and Domain Exporter), and Grafana for informative centralized dashboard visualization. The system is also integrated with early warning notifications via Telegram for rapid incident response. The result is a functional system with a centralized dashboard that visually displays the remaining validity period of assets using color markers (green for safe status, yellow for early warning, and red for critical status). System testing showed very high accuracy, reaching 100% for domains (MAE 0 days) and 99.45% for SSL certificates (MAE 1.0 days). This system has successfully transformed manual processes into automated and preventive ones, significantly mitigating the risk of human error and ensuring the reliability of digital services. Keywords: domain; grafana; monitoring; prometheus; SSL certificate. Abstrak: Pengelolaan manual masa berlaku domain dan sertifikat SSL rentan terhadap human error dan dapat menyebabkan gangguan layanan, seperti yang pernah terjadi di PT XYZ. Pendekatan reaktif yang mengandalkan notifikasi vendor terbukti tidak lagi memadai untuk menjamin kontinuitas operasional. Penelitian ini bertujuan merancang dan mengimplementasikan sistem pemantauan otomatis untuk mentransformasi pendekatan manual tersebut menjadi kerangka kerja keamanan yang preventif dan proaktif. Metode yang digunakan adalah implementasi stack open-source yang terdiri dari Prometheus untuk mengumpulkan metrik dari exporter spesialis (Blackbox dan Domain Exporter), serta Grafana untuk visualisasi dasbor terpusat yang informatif. Sistem ini juga diintegrasikan dengan notifikasi peringatan dini melalui Telegram untuk respons insiden yang cepat. Hasilnya adalah sebuah sistem fungsional dengan dashboard terpusat yang menampilkan sisa masa berlaku aset secara visual menggunakan penanda warna (hijau untuk status aman, kuning untuk peringatan dini, dan merah untuk status kritis). Pengujian sistem menunjukkan akurasi yang sangat tinggi, mencapai 100% untuk domain (MAE 0 hari) dan 99.45% untuk sertifikat SSL (MAE 1.0 hari). Sistem ini berhasil mengubah proses manual menjadi otomatis dan preventif, secara signifikan memitigasi risiko human error dan menjamin keandalan layanan digital. Kata kunci: domain; grafana; pemantauan; prometheus; sertifikat SSL.